Using software to improve first-year English majors' pronunciation: an action research at Hong Duc University - Trịnh, Thị Hằng (ĐHNN, 2017)
The firts part deals with rationale, purposes, research questions, scope, methods and design of the study. The secon part contains three chapters, in which chapter 1 reviews the literature focusing on the theoretical basis related to teahching pronunciation and using CALL programs in language learning and teaching, chapter 2 presents a detailed description of the research methodology, and chapter 3 discusses the findings of the study. The final part summarizes all the main ideas expressed throughout the research, provides pedagogical implications and suggests further research orientation.